ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL PERSAMAAN LINEAR DUA VARIABEL - Wahyu Gumelar; M. Afrilianto (IKIP Siliwangi, 2021)
Mathematics is a subject that has a very large role for the development of education in the current era. But in fact, it is still considered a difficult lesson to learn and not interesting because there are too many formulas to memorize. Where the reason for solving students' difficulties in completing the SPLDV material in junior high school is because it is easy to find in students' daily lives. The number of 20 students of class IX SMPN Satu Atap Karya Utama is the subject of the research. The research method uses descriptive qualitative, with instruments in it, namely test questions with specified indicators. The data analysis uses data reduction, data presentation, and drawing conclusions. After being studied, it was found that several students had problems with the SPLDV material story questions. Errors in student answers vary from the lack of students learning concepts from SPLDV, students are still confused in determining the right method to solve problems related to SPLDV, the next obstacle is the difficulty of students changing story questions into the process of mathematical modeling due to their lack of accuracy in reading questions related to the material. SPLDV.